Some theorems about the density of the Hecke zeta-zeros - Bulota, K. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: К. Булота. Теоремы о густоте нулей Z — функций Гекке K. Bulota. Hekės Z — funkcijų nulių tankio teoremos